2000
DOI: 10.3354/meps196253
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal patterns of habitat partitioning in a guild of southern California tidepool fishes

Abstract: Five species of fish, Clinocottus analis, Girella nigdcans, Hypsoblennius gilberti, Gobiesox rl~essodon, and Gibbonsia elegans, conlmonly occur in southern California's rocky intertidal zone. To examine the extent to which tidepool habitat is segregated by the 5 fishes, habitat partitioning patterns among and within the species were determined at 2 sites in San Diego. Fish density, species composition, and fish size were measured in 105 tidepools every 3 mo from November 1996 to August 1997. Hypotheses were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 26 publications
3
57
1
3
Order By: Relevance
“…The flooding of tidepools during high tides, which provides the access to fish to this ecosystem, is dependent upon factors such as tidal amplitude, local reef topography and distance from shore line (METAXAS & SCHEIBLING, 1993;MAHON & MAHON, 1994;DAVIS, 2000). Our results showed that higher diversity and abundance was attained at Pecém, where pools were shallower and closer to shore.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The flooding of tidepools during high tides, which provides the access to fish to this ecosystem, is dependent upon factors such as tidal amplitude, local reef topography and distance from shore line (METAXAS & SCHEIBLING, 1993;MAHON & MAHON, 1994;DAVIS, 2000). Our results showed that higher diversity and abundance was attained at Pecém, where pools were shallower and closer to shore.…”
Section: Discussionsupporting
confidence: 59%
“…and Engraulidae) for community composition was stronger for Iparana pools, which are located near the mouth of the Ceará River estuary, whereas tropical reef species, such as Stegastes fuscus (Cuvier, 1830), Serranus flaviventris, Chaetodon ocellatus, C. striatus, Myrichthys ocellatus, were found exclusively at Pecém. The environmental gradient provided by freshwater discharge, and subsequent changes in seawater chemistry and turbidity, could not only directly influence the environmental conditions at the pool areas, but also have a localized effect over the species source-pool, from which the tidepool community would draw its components (FUJI, 1988;METAXAS & SCHEIBLING, 1993;DAVIS, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Only with high temporal resolution sampling designs (e.g., monthly samples), could be achieved the record of opportunistic and transient fishes. (Gibson 1972, Barton 1982, Davis 2000, Castellanos-Galindo et al 2005, Cox et al 2010) and exposure to waves (Gibson 1972, Grossman 1982. For example, the tidepools in Cabo Branco (see Rosa et al 1997) are about 80-266 times voluminous than the sampled pools in Jericoacoara.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of trophic overlap provides information on the degree of dietary competition among the species (Colwell and Futuyma, 1971;Mayr and Berger, 1992). Resource partitioning in fish assemblages can be manifested in several ways, including the segregation of prey based on type or size and the partitioning of habitat, both temporally and spatially (Davis, 2000).…”
Section: Introductionmentioning
confidence: 99%